DEVELOPMENT OF STEM-BASED E-MODULES USING FLIP PDF PROFESSIONAL ON TEMPERATURE AND HEAT MATERIL - Azriyanti, Riza; Hendri, Menza; Rasmi, Dian Pertiwi (EduFisika: Jurnal Pendidikan Fisika, 2024)
This research aims to produce a STEM-based e-module on temperature and heat material and determine student perceptions. This research is development research that uses the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. However, this research is limited to the implementation stage. The test subjects for this research were class XI MIPA 6 students at Senior High School 3 Jambi City and class XI MIPA 3 students at Senior High School 11 Jambi City. The instruments used were media and material validation questionnaires and student perception questionnaires. Two types of data are collected, namely qualitative and quantitative. Qualitative data was obtained from media and material experts' criticism, comments, and suggestions. Then, quantitative data was obtained from the results of product validation by validation by media and material experts, as well as student perception questionnaires. The results of media expert validation by the two validators were 100% in the very good category. The results of material validation by the two validators were 70.83% in the good category and 97% in the very good category. The results of the analysis of student perceptions obtained an average score from the two schools, namely 84.05% and 86.97% in the very good category. The STEM-based electronic modules developed are valid and suitable for use to help students in the learning process, and the e-modules developed can be accessed offline via laptop/computer and online via cellphone by distributing links to students.